2019
DOI: 10.1111/ppl.12981
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic barriers, aquaporin gene expression and root and cell hydraulic conductivity in phosphate‐limited sheepgrass plants

Abstract: Mineral nutrient supply can affect the hydraulic property of roots. The aim of the present work on sheepgrass (Leymus chinensis L.) plants was to test whether any changes in root hydraulic conductivity (Lp; exudation analyses) in response to a growth‐limiting supply of phosphate (P) are accompanied by changes in (1) cell Lp via measuring the cell pressure, (2) the aquaporin (AQP) gene expression by performing qPCR and (3) the formation of apoplastic barriers, by analyzing suberin lamella and Casparian bands vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…In agreement with our results, Paranidharan et al [72] found increased POX activities in rice in response to infection by Rhizoctonia solani. According to these results, we can speculate that increased lignin synthesis during both salt stress and pathogen infection in order to establish an apoplastic barrier and to make the cell wall less permeable to water loss might also be the case in our study [73]. On the other hand, POX activity of the all Trichoderma-treated plants under stress was lower than that of the control levels.…”
Section: Discussionmentioning
confidence: 49%
“…In agreement with our results, Paranidharan et al [72] found increased POX activities in rice in response to infection by Rhizoctonia solani. According to these results, we can speculate that increased lignin synthesis during both salt stress and pathogen infection in order to establish an apoplastic barrier and to make the cell wall less permeable to water loss might also be the case in our study [73]. On the other hand, POX activity of the all Trichoderma-treated plants under stress was lower than that of the control levels.…”
Section: Discussionmentioning
confidence: 49%
“…The regulation of aquaporins membrane (localized at the plasma membrane) that control water movement within/out of the plants and influence the hydraulic property of roots are affected. The expression of aquaporin genes coding for protein membranes responsible for apoplastic barriers synthesis decreased (Li et al, 2020). Specifically, the genes encoding the 3-Pi dehydrogenase bound synthesis LcPIP1;1, LcPIP2;1, LcPIP2;4, HvPIP2;2, and HvPIP2;5 decreased.…”
Section: Genes Involved In Pi-dependent Regulation Of Plant Stressesmentioning
confidence: 99%
“…A recent study has highlighted new candidate genes expressed during exposure of plants to combined Pi starvation and drought stresses (Armand et al, 2019;Li et al, 2020). The regulation of aquaporins membrane (localized at the plasma membrane) that control water movement within/out of the plants and influence the hydraulic property of roots are affected.…”
Section: Genes Involved In Pi-dependent Regulation Of Plant Stressesmentioning
confidence: 99%
“…Also, P starvation could cause combined changes in root Lp and aquaporins gene expression together with the formation of endodermal apoplastic barriers in roots (Li et al 2019a). In fact, recently, Li et al (2019a, b, c) showed a decrease in the gene expression of six PIPs aquaporins ( LcPIP1;1 , LcPIP1;4 , LcPIP2;1 , LcPIP2;4 , Put‐LcPIP2;2 and Put‐LcPIP2;5 ) in Leymus chinesis L. under low P availability. Indeed, P starvation may also modulate aquaporins activity, due to changes in their phosphorylation status (Wang et al 2016).…”
Section: The Influence Of Macronutrient Deficiencies On the Interaction Of Their Transporters And Aquaporinsmentioning
confidence: 99%